2016
DOI: 10.1007/s00167-016-4157-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased lateral tibial slope predicts high-grade rotatory knee laxity pre-operatively in ACL reconstruction

Abstract: Prospective diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 28 publications
(42 reference statements)
7
75
0
1
Order By: Relevance
“…In fact, unaddressed meniscal tears, underappreciated meniscocapsular injuries, increased posterior tibial slope, and anterolateral capsular injuries have all been demonstrated to play a role in rotatory knee stability. 3,10,2328,30,38 …”
mentioning
confidence: 99%
“…In fact, unaddressed meniscal tears, underappreciated meniscocapsular injuries, increased posterior tibial slope, and anterolateral capsular injuries have all been demonstrated to play a role in rotatory knee stability. 3,10,2328,30,38 …”
mentioning
confidence: 99%
“…Bony features such as increased posterior tibial slope and a deep lateral femoral notch have been associated with increased ACL injury risk and rotatory knee instability. 5761, 23 In addition, stereo fluoroscopy at our institution has demonstrated that posterior tibial slope correlates with knee kinematics in ACL reconstructed patients (Figure 5). 23 In cases of excessive posterior tibial slope, an anterior closing wedge tibial osteotomy may be indicated.…”
Section: Technical Considerations For Revision Acl Reconstruction Surmentioning
confidence: 92%
“…5761, 23 In addition, stereo fluoroscopy at our institution has demonstrated that posterior tibial slope correlates with knee kinematics in ACL reconstructed patients (Figure 5). 23 In cases of excessive posterior tibial slope, an anterior closing wedge tibial osteotomy may be indicated. Similarly, patients with excessive varus malalignment may experience greater in-situ graft forces, 62 and concomitant proximal tibial osteotomy may be needed.…”
Section: Technical Considerations For Revision Acl Reconstruction Surmentioning
confidence: 92%
See 1 more Smart Citation
“…Os dados obtidos após a análise dos valores do "slope" lateral estão de acordo com a maioria dos trabalhos publicados recentemente (BEYNNON et al, 2014;FEUCHT et al, 2013;HOHMANN et al, 2011;RAHNEMAI-AZAR et al, 2017;ZENG et al, 2014). O compartimento lateral é mais móvel e tem maior efeito sobre a estabilidade rotacional no joelho.…”
Section: Método De Medição Do "Slope" Tibialunclassified